Design, synthesis, and biological evaluation of novel Bcr-AblT315I inhibitors incorporating amino acids as flexible linker. (15th October 2021) - Pan, Xiaoyan; Liu, Nanxin; Zhang, Qingqing; Wang, Kai; Li, Yanchen; Shan, YuanYuan; Li, Zilong; Zhang, Jie
Graphical abstract: A series of novel Bcr-Abl T315I inhibitors with amino acids as flexible linker were developed and performed biological evaluation in vitro . Abstract: Despite the success of imatinib in CML therapy through Bcr-Abl inhibition, acquired drug resistance occurs over time in patients. In particular, the resistance caused by T315I mutation remains a challenge in clinic. Herein, we embarked on a structural optimization campaign aiming at discovery of novel Bcr-Abl inhibitors toward T315I mutant based on previously reported dibenzoylpiperazin derivatives. We proposed that incorporation of flexible linker could achieve potent inhibition of Bcr-Abl T315I by avoiding steric clash with bulky sidechain of Ile315. A library of 28 compounds with amino acids as linker has been developed and evaluated. Among them, compound AA2 displayed the most potent activity against Bcr-Abl WT and Bcr-Abl T315I, as well as toward Bcr-Abl driven K562 and K562R cells. Further investigations indicated that AA2 could induce apoptosis of K562 cells and down regulate phosphorylation of Bcr-Abl. In summary, the compounds with amino acid as novel flexible linker exhibited certain antitumor activities, providing valuable hints for the discovery of novel Bcr-Abl inhibitors to overcome T315I mutant resistance, and AA2 could be considered as a candidate for further optimization.